Pronounciation Error in Speaking Performance of Seafarer Students - Haryani Haryani; Rachmat AW; Ali Rafsanjani (Marine Science and Technology Journal, 2020)
Pronunciation can be an important aspect of learning to speak. When the pronunciation is wrong, it may interfere with the listener's understanding of the message. The students also experienced some difficulties in pronouncing some words, especially in vowels and consonants. The purpose of this study was to determine the pronunciation errors of seafaring students of Polytechnic Bumi Akpelni Semarang, and to find out the most dominant error. The author classifies pronunciation errors into four categories based on Dulay, Burt & Karshen's theory. This study uses qualitative research, and content analysis as a method of analyzing and interpreting data from speaking transcripts of KPN Polytechnic Bumi Akpelni Semarang students. There were 16 students who were the research subjects. The author analyzes the pronunciation of students' mistakes from their transcript of their speech. The results of this study are, there are 46 data consisting of 28 (60%) misformation, 12 (26.1%) additional, 6 (13%) negligence and 0 (0%) misordering. The most dominant error is misformation error and there is no misordering error in this study. In fact, students sometimes pronounce English words correctly spontaneously, even though they don't know how to pronounce correctly and only use their feelings.